C—H...O and C—H...N interactions in three hexahydrocycloocta[b]pyridine‐3‐carbonitriles. Issue 2 (15th February 2014) - Vishnupriya, R.; Suresh, J.; Maharani, S.; Kumar, R. Ranjith
<x xml:space="preserve">Abstract</x> The structures of three new pyridine derivatives, 2‐methoxy‐4‐(4‐methoxyphenyl)‐5, 6, 7, 8, 9, 10‐hexahydrocycloocta[b]pyridine‐3‐carbonitrile, C20H22N2O2, (I), 2‐ethoxy‐4‐(3‐nitrophenyl)‐5, 6, 7, 8, 9, 10‐hexahydrocycloocta[b]pyridine‐3‐carbonitrile, C20H21N3O3, (II), and 2‐ethoxy‐4‐(4‐methoxyphenyl)‐5, 6, 7, 8, 9, 10‐hexahydrocycloocta[b]pyridine‐3‐carbonitrile, C21H24N2O2, (III), differ in the nature of the substituents either at the 2‐position of the central pyridine ring or on the pendent aryl ring. This simple change in the structure substantially alters the intermolecular interaction patterns. The substituted phenyl group adopts a synclinal geometry with respect to the plane of the pyridine ring in all three compounds. In (I), a C—H...N interaction results in a one‐dimensional chain parallel to the b axis. In (II), there are two C—H...N(nitrile) interactions from different symmetry‐related molecules, resulting in a two‐dimensional network parallel to the bc plane. There is also a weak C—H...O interaction from the ethoxy group to an adjacent nitro O atom. The present work is an example of how the simple replacement of a substituent in the main molecular scaffold may transform the structure type, paving the way for a variety of supramolecular motifs and consequently altering the complexity of the intermolecular interaction patterns.